Cultura universitária e experiência de juventude de estudantes do segundo e terceiro ano de geografia da FCT/UNESP-Presidente Prudente - Silva, João Pedro Turino [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The research focuses on the university culture that is constituted in the Geography course of the FCT/UNESP, Presidente Prudente, more particularly the experience that young students of the second and third years of the course have of it (initially, before the Covid 19 pandemic, the idea was to work with the first and second years), precisely those who are going through the process of insertion into university life, coming from life trajectories and with very diverse future projects. The main questions that guided the research were: who are the young people who arrive at the Geography course at the FCT/UNESP and what were their previous experiences as young people and what experiences did they have when they entered the course? What would be the undergraduate Geography course at FCT/UNESP as a specific socio-spatial and cultural context that would make this youth experience unique? How do students in their diversity articulate their specificity to their experiences as Geography students? To answer these questions, we followed an investigative path that articulated quantitative and qualitative strategies of information production. On one hand, we worked both with secondary data from UNESP itself, and with questionnaires applied to the universe of students, the focus of the research. On the other hand, we carried out qualitative research, with focus groups and interviews. However, in the context of the pandemic, our form of access to the students was remote, through the Google Meet platform. As a result of all this effort, we were able to draw a common profile of the 2nd and 3rd year students of the Geography course and analyze their diverse trajectories. We found a university culture specific to the Geography course, which has its own spaces for meeting and sociability, but which is often confused with a university culture generalized in all courses at the FCT/UNESP. With this research, we hope to bring a contribution both to the field of "Geography of Youth" studies and to the Geography course itself, which will be able to know other facets of the student universe and thus, to rethink pedagogical strategies and actions to expand the dialogue with students and strategies against school dropout (so present in the course).

A pesquisa tem como foco a cultura universitária que se constitui no curso de Geografia da Faculdade de Ciências e Tecnologia, da Universidade Estadual Paulista “Júlio de Mesquita Filho” (FCT/UNESP), Presidente Prudente, mais particularmente a experiência que têm dela jovens estudantes do segundo e terceiro anos do curso (inicialmente, antes da pandemia de Covid 19, a ideia era trabalhar com o primeiro e segundo anos), justamente aqueles que estão passando pelo processo de inserção na vida universitária, vindos de trajetórias de vida e com projetos de futuro muito diversos. As questões principais que orientaram a pesquisa foram: quem são os jovens que chegam ao curso de Geografia da FCT/UNESP e quais eram suas experiências prévias de juventude e que experiências passaram a ter quando ingressam no curso? O que seria a graduação em Geografia da FCT/UNESP enquanto contexto socioespacial e cultural específico, que tornaria esta experiência de juventude singular? Como os estudantes em sua diversidade articulam sua especificidade às experiências como estudantes de Geografia? Para responder estas questões, seguimos um percurso investigativo que articulou estratégias quantitativas e qualitativas de produção de informação. Por um lado, trabalhamos tanto com dados secundários da própria UNESP, quanto com questionários aplicados ao universo dos estudantes, foco da pesquisa. Por outro lado, realizamos uma pesquisa qualitativa, com grupos focais e entrevistas. Contudo, no contexto da pandemia, nossa forma de acesso aos estudantes se deu de forma remota, pela plataforma do google meet. Como resultado, conseguimos traçar um perfil dos estudantes do 2° e 3° ano do curso de Geografia e analisar suas diversas trajetórias; constatamos uma cultura universitária própria do curso de Geografia, que tem seus espaços de encontro e sociabilidade, mas que muitas vezes se confunde com uma cultura universitária generalizada em todos os cursos da FCT/UNESP. Com a pesquisa, esperamos trazer uma contribuição tanto ao campo de estudos da “Geografia das Juventudes”, quanto para o próprio curso de Geografia, que poderá conhecer outras facetas do universo estudantil e assim, repensar estratégias pedagógicas e ações para ampliar o diálogo com os estudantes e estratégias contra a evasão escolar (tão presente no curso).
University culture and youth experience of 2° and 3° grade geography students of FCT/UNESP-Presidente Prudente
Keywords: University culture; Geography students; Youth; Cultura universitária; Estudantes de geografia; Juventudes; Unesp Presidente Prudente